2017
DOI: 10.1080/10934529.2017.1356191
|View full text |Cite
|
Sign up to set email alerts
|

Redox-mediator-free degradation of sulfathiazole and tetracycline usingPhanerochaete chrysosporium

Abstract: The removal of two of the most commonly used antibiotics, tetracycline (TC) and sulfathiazole (STZ), using laccase-producing Phanerochaete chrysosporium was studied in liquid-phase batch experiments in the absence of any synthetic redox mediator. The removal of STZ and TC from single antibiotic spikes varied from 97.8% to 15.4% and 98.8% to 31%, respectively, with increasing initial doses of 10-250 mg L within 14 days of incubation. The enzyme activity of P. chrysosporium was only minimally influenced by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Our results indicated that combined the three metabolic inhibitors prevented the biofilm formation for more than 96 h (Figure S5). In fact, many metabolic inhibitors can be degraded by particular microorganisms; for instance, Phanerochaete chrysosporium is capable of removing ST (Kwak et al 2017 ). Further investigation of their degradation rates and stability is necessary to ensure long-term efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that combined the three metabolic inhibitors prevented the biofilm formation for more than 96 h (Figure S5). In fact, many metabolic inhibitors can be degraded by particular microorganisms; for instance, Phanerochaete chrysosporium is capable of removing ST (Kwak et al 2017 ). Further investigation of their degradation rates and stability is necessary to ensure long-term efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The ratio of substrate to biocatalyst appears relevant with regard to enzyme saturation and inhibition effects. 13 Furthermore, because fungi require additional nutrients to grow and survive, these carbon sources are metabolized in competition with trace concentrations of tetracyclines in the environment, which may reduce overall removal efficiency of tetracyclines. This illustrates the complexity of biotransformation reactions and provides initial explanations for the observed differences in conversion rates between trials.…”
Section: Challengesmentioning
confidence: 99%
“…Consequently, some results seem not to be confirmable and even contradictory. For example, the redox mediator ABTS showed negative effects on laccase activity, although its use is generally a promising approach to enhance the transformation of tetracyclines by laccases. , The ratio of substrate to biocatalyst appears relevant with regard to enzyme saturation and inhibition effects . Furthermore, because fungi require additional nutrients to grow and survive, these carbon sources are metabolized in competition with trace concentrations of tetracyclines in the environment, which may reduce overall removal efficiency of tetracyclines.…”
Section: Analytical and Biotechnological Challengesmentioning
confidence: 99%